Analisis Efektivitas Kebijakan Pemutihan Pajak Terhadap Penerimaan Pajak Kendaraan Bermotor: Studi pada Badan Pendapatan Daerah Provinsi Kalimantan Timur - Dewi Ratna Rahimi; Rusliansyah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The purpose of this study is to determine the effectiveness level of the tax whitening policy, which includes relief and elimination of tax penalties, on motor vehicle tax revenue, as well as to compare the tax revenue targets before and after the implementation of the policy. This research employs a descriptive quantitative approach using secondary data, including the target and realization of motor vehicle tax revenue and tax arrears from 2019 to 2024. The analysis methods used include calculating the tax arrears clearance rate, the effectiveness of tax revenue collection, and the contribution of arrears clearance to total revenue. The results show that the effectiveness of motor vehicle tax revenue collection was categorized as very effective during the observed period, with actual revenues exceeding the targets each year. However, the contribution of arrears clearance to total revenue tended to decline and remained low, indicating that most revenue was derived from taxpayers who paid on time.